The Neo-Khawarij of the Azariqah: a political study - Mahayudin Haji. Yahya, (Universiti Kebangsaan Malaysia, 1981)
When 'Ali was recognised as Caliph, all the qurra' paid their oath of allegiance to him at first but then the majority of these qurra' turned against him after his acceptance of the arbitration of Siffin, because they realised that he was not interested in restoring their lost priviliges in the Sawas (Iraq) during the reign of 'Uthman they became Khawarij and declared war on both 'Ali and Mu'awiyah. The Kharijite opposition continued throughout the reigns of Mu'awiyah and Ibn al-Zubayr. But because their number was small they decided to enter into alliance with another movement led by tribesmen of central and eastern Arabia, mainly from Hanifah, 'Abd al-Qays and Tamim. Their interest had nothing in common with that of the early-Khawarij. However, all these rebels are referred to by our sources as the Azariqah.